Systemic Antifungal Therapy for Invasive Pulmonary Infections - Ronen Ben-Ami (Journal of Fungi, 2023)
Antifungal therapy for pulmonary fungal diseases is in a state of flux. Amphotericin B, the time-honored standard of care for many years, has been replaced by agents demonstrating superior efficacy and safety, including extended-spectrum triazoles and liposomal amphotericin B. Voriconazole, which became the treatment of choice for most pulmonary mold diseases, has been compared with posaconazole and itraconazole, both of which have shown clinical efficacy similar to that of voriconazole, with fewer adverse events. With the worldwide expansion of azole-resistant Aspergillus fumigatus and infections with intrinsically resistant non-Aspergillus molds, the need for newer antifungals with novel mechanisms of action becomes ever more pressing.